Let $(M,g)$ be a Riemannian manifold.

From John Lee's Riemannian Manifolds, the divergence operator $\text{div}:\Gamma(TM)\to C^{\infty}(M)$ is defined to be the map that sends $X$ to the unique function $\text{div} X$ such that $$(\text{div} X) \,dV_g = d(X\lrcorner \,dV_g),$$ where $dV_g$ is the volume form and $\lrcorner$ denoted the interior multiplication.

The above seems pretty complicated to me. Recently, I have found a much more accessible definition, i.e. $$ \text{div} = \text{tr} \circ \nabla $$ where $\nabla$ denotes the total covariant derivative.

How do we show that these definitions are equivalent?

It seems to me that the books I found only use either one of these and do not mention the other.


We can show that this equality holds at any point of $M$ by computing in local coordinates. At the point $p\in M$ we use Riemannian normal coordinates, which have the property that the metric at $p$ is given by the identity matrix, $g_{ij}(p)=\delta_{ij}$, and that the derivatives of the metric coefficients are zero at $p$, as are the Christoffel symbols. With this we can write \begin{equation} \text{tr}\ \nabla X (p) = \sum_{i=1}^n g(\nabla_{\partial_i} X,\partial_i)(p) = \sum_{i=1}^n(\partial_i X^j)(p)\delta_{ij} = \sum_{i=1}^n\partial_i X^i(p). \end{equation} On the other hand, we have $\text{det}(g)(p)=1$ in these coordinates, and since the determinant is polynomial in the entries of the matrix of $g$, all its partial derivatives vanish at $p$ in these coordinates. With $dV_g = \sqrt{|g|}dx^1\wedge\ldots\wedge dx^n$ we can write \begin{equation} X\lrcorner\ dV_g = \sqrt{|g|}\sum_{i=1}^n(-1)^{i+1}X^i dx^1\wedge\ldots\widehat{dx^i}\wedge\ldots\wedge dx^n, \end{equation} where the hatted factor is the one excluded from the wedge product. Noting that the partial derivatives of $\sqrt{|g|}$ vanish at $p$ we can write \begin{equation} d(X\lrcorner\ dV_g)(p) = \sum_{i=1}^n(-1)^{i+1}(\partial_j X^i)(p)dx^j\wedge dx^1\wedge\ldots\widehat{dx^i}\wedge\ldots\wedge dx^n. \end{equation} All the terms where $i\neq j$ will be zero by antisymmetry of $\wedge$. Permuting the leftmost factor $dx^j$ to the place of the hatted factor we change sign $i-1$ times, so the sign factors cancel. We are left with \begin{equation} d(X\lrcorner\ dV_g)(p) = \left(\sum_{i=1}^n(\partial_i X^i)(p)\right)\ dx^1\wedge\ldots\wedge dx^n = \text{tr}\ \nabla X(p)\ dV_g. \end{equation}


We can work locally since everything there is a tensor. Assume $(E_1,\ldots,E_n)$ is a local orthonormal frame field, such that $(\nabla_{E_j}E_i)_p = 0$ for some $p \in M$. We will check the equality at $p$.

If $(\theta^1,\ldots, \theta^n)$ is the corresponding coframe, then $$dV_g = \theta^1 \wedge \cdots \wedge \theta^n.$$We can write $X = \sum_{i=1}^n \theta^i(X) E_i$, and we also know that $\theta^i(X) = \langle X,E_i\rangle$, by orthonormality. On one hand, it is easy (?) to check that $${\rm tr}(\nabla X) = \sum_{i=1}^n \langle \nabla_{E_i}X,E_i\rangle,$$so let's compute the other expression. We start computing the interior derivative $$\begin{align}\iota_X(dV_g) &= \iota_X(\theta^1 \wedge \cdots \wedge \theta^n) \\ &= \sum_{i=1}^n (-1)^{i-1} \theta^1 \wedge \cdots \wedge \iota_X(\theta^i)\wedge \cdots \wedge \theta^n \\ &= \sum_{i=1}^n (-1)^{i-1} \theta^i(X) \;\theta^1\wedge \cdots \wedge\widehat{\theta^i} \wedge \cdots \wedge \theta^n, \end{align}$$where the hat denotes omission. Then we compute the exterior derivative of that: $$\begin{align} d(\iota_X(dV_g)) &= \sum_{j=1}^n \sum_{i=1}^n (-1)^{i-1} E_j(\theta^i(X)) \; \theta^j \wedge \theta^1\wedge \cdots \wedge\widehat{\theta^i} \wedge \cdots \wedge \theta^n \\ &= \sum_{i=1}^n (-1)^{i-1} E_i(\theta^i(X)) \;\theta^i\wedge \theta^1\wedge \cdots \wedge\widehat{\theta^i} \wedge \cdots \wedge \theta^n \\ &= \sum_{i=1}^n E_i(\theta^i(X)) \;\theta^1\wedge \cdots \wedge \theta^n \\ &= \left(\sum_{i=1}^n E_i(\theta^i(X))\right) \theta^1\wedge \cdots \wedge \theta^n \\ &= \left(\sum_{i=1}^n E_i(\theta^i(X))\right) dV_g.\end{align}$$The result follows since at $p$ we have $$(E_i)_p(\theta^i(X)) = \langle (\nabla_{E_i}X)_p,(E_i)_p\rangle + \langle X, (\nabla_{E_i}E_i)_p\rangle =\langle (\nabla_{E_i}X)_p,(E_i)_p\rangle. $$The result is also true for pseudo-Riemannian manifolds, with a slight adaptation of the calculations done above.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.